Mediasi Batik sebagai Budaya Populer: dari Habitus ke Gaya Hidup - Fionna Christabella (Program Studi Ilmu Komunikasi, 2008)
This article explores the mediations of batik commodifications and its implications in popular culture. In some media, batik that commodified forming the assumptions that influence the consumption patterns, life styles, and strategies of social stratification. The media prepares the change and different meaning of batik in contemporary society. Now, batik as fashion can't be understood and identification as material identity of local culture, like batik from Solo or from Pekalongan. Furthermore, some media influence new and popular definitions of batik in contemporary Indonesian society. The definitions are all meanings of batik that relate from commodification in media and modes of consumption in society.